Caracterização fisiológica e avaliação do transcriptoma de linhagens de Saccharomyces cerevisiae termotolerantes isoladas durante a produção industrial de etanol - Prado, Cleiton Dias do (Universidade Federal de São Carlos, 2022)
The use of thermotolerant yeast strains can improve productivity in the ethanol production process, allowing fermentation to occur at temperatures above 40°C. This characteristic can benefit, for example, the production of bioethanol and allow simultaneous saccharification and fermentation (SSF) of starch or lignocellulosic biomass. In addition, a thermotolerant strain can increase ethanol yield levels and also minimize the use of vat cooling systems and consequently reduce water use, contributing to cost reduction and also to the environment. The aim of this study was to identify and characterize the physiology of a new thermotolerant strain (LBGA-01) isolated from the ethanol production process capable of fermenting at 40°C and also to evaluate the transcriptome of this strain during fermentations carried out in chemostats. So that the strain could be characterized from the physiological and molecular point of view, growth experiments were carried out under laboratory conditions, such as growth tests in the presence of glucose (4 and 8%) and also in the presence of inhibitors (sucrose, ethanol, furfural, lactic acid, and acetic acid). The expression of genes involved in fermentation efficiency was analyzed by qPCR. To have a better understanding of yeast physiology, fermentations in chemostats were performed and the metabolites were analyzed by HPLC. Cells originating from the steady state of fermentations in chemostats had their RNA extracted for transcriptome analysis and subsequently, the bioinformatics analyzes were carried out in partnership with CBMEG/UNICAMP. To simulate real conditions of the industrial process, fermentations with cycles (4 cycles) of cells and acid treatment were also carried out at 30 and 40°C using wort (19 brix) as fermentation medium. The results presented in this study show that the LBGA-01 strain has a good cell growth rate at 30 and 40°C and is more resistant to high concentrations of sucrose (30%), furfural (0.9 mM), and ethanol (16 %) than the industrial strain CAT-1. Furthermore, this strain was able to alter the expression pattern of genes involved in sucrose assimilation (SUC2 and AGT1). Genes related to the production of proteins involved in the production of secondary fermentation products were also differentially regulated at 40°C, with reduced expression of genes involved in the formation of glycerol (GPD2), acetate (ALD6 and ALD4), and acetyl-coenzyme A synthetase 2 (ACS2). Fermentation tests in chemostats showed that LBGA-01 performed excellently at ethanol formation rates at 40°C (11.50 mmol/g/h). Furthermore, when compared to the industrial strains CAT-1 and PE-2, the LBGA-01 strain showed better ethanol yield at 40°C (0.478 g ethanol/g glucose). The transcriptome results showed that the thermotolerant strain LBGA-01 modulates the activation of genes by altering metabolic pathways during fermentation at high temperatures, increasing its resistance to high concentrations of ethanol, sugar, lactic acid, and acetic acid. The results showed that the LBGA-01 strain, when subjected to high temperatures, has a more intensified regulation of genes involved in cell wall integrity (SVS1; MCH5) and in lipid biosynthesis (ROX1; ERG3; ERG5; ERG10 and ERG13). In addition, it was also possible to observe the expression of genes related to fermentative capacity (TOS3) corroborating with previous results analyzed by q-PCR. The results indicate that this new strain isolated from ethanol production, has high robustness in the presence of inhibitors of the ethanol production process (sucrose, ethanol, and furfural), in addition to presenting good levels of ethanol yield and cell growth at the control temperature (30°C) and stress temperature (40°C), with interesting characteristics of gene expression, and also the transcription of genes involved with cell resistance to 40°C during fermentations in chemostats. When subjected to conditions simulating the industrial process, the LBGA-01 strain seems to adapt to the conditions of recycling and acid treatment, producing good levels of ethanol yield based on theory. Therefore, from a technological point of view, the LBGA-01 strain has the potential for scientific and industrial application and can be used to improve ethanol production in Brazil.
Physiological characterization and transcriptome evaluation of thermotolerant Saccharomyces cerevisiae strains isolated during industrial ethanol production
Keywords: Saccharomyces cerevisiae; Termotolerante; Etanol; Fermentação; Transcriptoma; Quimiostato; Genes; CIENCIAS BIOLOGICAS::BIOQUIMICA::BIOLOGIA MOLECULAR